2020
DOI: 10.1029/2019gl086725
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions: Remote Mapping and Source Quantification Using an Open‐Path Laser Dispersion Spectrometer

Abstract: Reducing man-made greenhouse gas emissions depends on the effective detection and location of sources. We present a new method that remotely detects, locates, and quantifies gas emission rates by sequentially steering an optical beam between multiple retro-reflectors. The novel open-path laser gas sensor uses Laser Dispersion Spectroscopy (LDS), with seven beams up to 98 meters long deployed across open, flat terrain. LDS offers high precision (10-20 ppb), high dynamic range and linearity, enhanced immunity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This work followed earlier “proof-of-concept” tests that demonstrated the effectiveness of the technique. 19 The new experiments incorporated improved sensor precision, refinements to the MCMC analysis, and inclusion of blind releases as a more objective measure of performance. The experimental arrangement is shown in Figure 1 .…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This work followed earlier “proof-of-concept” tests that demonstrated the effectiveness of the technique. 19 The new experiments incorporated improved sensor precision, refinements to the MCMC analysis, and inclusion of blind releases as a more objective measure of performance. The experimental arrangement is shown in Figure 1 .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Seven eye-safe beam paths radiate from the sensor to 5 cm aperture corner cube retroreflectors. From the demonstration study, 19 seven beams were found to be a good compromise to target a few-meter spatial resolution on locating sources. Path lengths ranged from 99.43 to 50.26 m. A 3D ultrasonic anemometer was installed at the center of the beam array, and it measured wind velocity in the horizontal and vertical planes at 20 Hz.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other works in the literature where emissions are detected, quantified, mapped, or localized include: A mid-wave infrared (MWIR) camera was used to compare eight supervised multivariate methods for detecting oil spills along the coastline in [41]. Using an array of stationary laser fetches, a controlled release emission is estimated using a Bayesian Markov chain Monte Carlo (MCMC) approach in [42]. There have been several works devoted to gas distribution mapping (GDM) using the Kernel DM/V methodology [43], including simultaneous localization and mapping (SLAM) [44].…”
Section: Introductionmentioning
confidence: 99%